Active Management Reduces the Incidence of Recurrent Pre-eclampsia and Improves Maternal and Fetal Outcomes in Women With Recurrent Pre-eclampsia - Dong, Xin; Han, Min; Zeb, Shahn; Tong, Mancy; Li, Xuelan; Chen, Qi (Frontiers in Medicine, 2021)
Background: Women with previous preeclampsia are at an increased risk of developing recurrent preeclampsia. Intervention with low-dose aspirin had been recommended to reduce the incidence of recurrent preeclampsia. However, the association between interventions and maternal and neonatal outcomes in subsequent pregnancies in women with previous preeclampsia has not been fully studied. Methods: In this prospective study, a total of 41 patients with previous preeclampsia received low dose aspirin and active management (including psychological and physiological intervention), between 10 to 28 weeks until 32 to 34 weeks in our regional referral hospital. The recurrence of preeclampsia and maternal and neonatal outcomes in this pregnancy were analyzed and compared to our previous study which reported a 60% recurrence of preeclampsia in our regional referral hospital. Results: Thirteen women with previous preeclampsia developed recurrent preeclampsia. The time of onset or severity of preeclampsia in the previous pregnancy was not associated with the incidence of recurrent preeclampsia. The time of onset of previous preeclampsia was also not associated with the time of onset in subsequent preeclampsia. However, the number of severe recurrent preeclampsia was significantly reduced, compared to their first pregnancies. The number of SGA and stillbirth/neonatal death was also significantly reduced in recurrent preeclampsia that was actively managed, compared to their first pregnancies. Conclusion: Despite the small sample size included in this study, our study demonstrates that active obstetric management reduces the incidence of recurrent preeclampsia, compared to our previous study, and reduces the severity of recurrent preeclampsia. It also improves neonatal outcomes in recurrent preeclampsia. However, because of no controls in this study, our findings need to confirmed by a case-control or randomized clinical trial study.